In Vitro Selection of New DNA Aptamers for Human Vascular Endothelial Growth Factor 165. (30th March 2020) - Manochehry, Sepehr; Gu, Jimmy; McConnell, Erin M.; Salena, Bruno J.; Li, Yingfu
Abstract: Two DNA aptamers that bind the heparin‐binding domain (HBD) of the human vascular endothelial growth factor 165 (VEGF‐165) have been previously reported. Although VEGF‐165 is a homodimeric protein and the two aptamers have different sequences and secondary structures, the aptamers appear to occupy the same binding site and cannot form a 2 : 1 aptamer/protein complex, thus making them unsuitable for creating a higher‐affinity dimeric DNA aptamer. This has motivated us to conduct a new in vitro selection experiment to search for new VEGF‐165‐binding DNA aptamers with different properties. We undertook a multistream selection strategy in which the concentration of VEGF‐165 was varied significantly. We carried out 11 rounds of selection, and next‐generation sequencing was conducted for every round in each stream. From comprehensive sequence analysis, we identified four classes of DNA aptamers, of which two were reported before, but two are new DNA aptamers. One of the new aptamers exhibits a unique property that has never been observed before: it is capable of forming the 2 : 1 aptamer/protein complex with VEGF‐165. This work has expanded the repertoire of VEGF‐165‐binding DNA aptamers and creates a possibility to engineer a higher affinity homodimeric aptamer for VEGF‐165. Abstract : Through concentration‐varying selection and bioinformatic analyses, we have identified four classes of DNA aptamers. One of the two new classes is unique in that it can form a 2 : 1 complex with the homodimeric protein VEGF‐165. This work has thus expanded the repertoire of anti‐VEGF‐165 DNA aptamers and created the possibility to engineer a higher‐affinity homodimeric aptamer for VEGF‐165.